Community pharmacist‐led clinical services: physician's understanding, perceptions and readiness to collaborate in a Midwestern state in the United States. (7th December 2017) - Gordon, Cameron; Unni, Elizabeth; Montuoro, Jaime; Ogborn, Diane B.
Abstract: Objectives: Many pharmacists are actively enhancing their role in the delivery of health care by offering a variety of pharmacist‐led clinical services. The delivery of these services within community pharmacies can contribute to overcoming the cost and accessibility challenges currently facing U.S. health care, especially when pharmacist–physician collaborative efforts are utilized. The study purpose was to identify general and family practice physicians' awareness of pharmacists' delivery of clinical services, uncover their perceived barriers to collaboration with community pharmacists, and collect their input on how to overcome such barriers in order to better understand how pharmacist‐led clinical services can be integrated, improved and more widely utilized as a healthcare delivery mechanism. Methods: Semi‐structured interviews were performed at the physicians' place of practice to assess (1) family practice and internal medicine physicians' knowledge of pharmacists' education, clinical training, and role in the healthcare team; (2) their perceptions and barriers towards pharmacist‐delivered clinical services and physician–pharmacist collaboration; and (3) their recommendations to improve physician–pharmacist collaboration. The data were analysed qualitatively to identify and categorize themes. Key findings: Thirteen physicians were interviewed. While nearly all physicians were aware of pharmacists' level of education, most were not aware of the level of clinical training pharmacists receive. Only half of the physicians were able to provide a definition or example of collaborative practice agreements, although most recognized value and benefit when the definition and examples were provided to them. The commonly perceived barriers for collaboration were concern over loss of communication, hesitancy to relinquish control and lack of confidence in pharmacists' clinical judgement. Conclusion: The study results emphasize the need to develop strategies to improve collaborative relationships between physicians and pharmacists. To encourage collaboration, pharmacists must take a proactive approach to increasing awareness of their clinical knowledge and training, the benefits and value of collaborative practice and the opportunities for it.